(untitled) (Педагогіка вищої та середньої школи, 2007)
The article deals with the re-establishment of the Ukrainian school in the above-mentioned period with taking into consideration the social and political situation in the country. The system of education was aimed at acquiring by rising generation professional knowledge and skills as early as possible. Labour principle of educational re-establishment predominated in applying methods of teaching.